Development of an android application and a cloud based server for a real time locating system using RFID - Kulkarni Ahilya Subhash (2016)
Asset tracking in Real Time Locating Systems (RTLS) plays a critical role in indoor environments in sectors such as medical, logistics, manufacturing and inventory management. RFID tags are attached to objects or people that have to be tracked and the signals from these tags are sent wirelessly to the readers. The location information is also stored in a central database which is accessible to the administrator for monitoring and tracking. This project aims at the Android development of an asset tracking application and the server side development for the application in cloud using the Google Cloud Platform. Mobile Computing as a computing paradigm is currently one of the largest areas being researched as it is an attractive to the traditional server environments in terms of scalability, accessibility and ease of usage. In this project, we aim to explore the concept of mobile cloud computing as a whole with its service models, providers, accessibility models and specifically the platform services offered by the Google App Engine and Google Datastore - a database service to provide a backend solution to our RFID asset tracking Android application. Also, a certain amount of research is done on self-localization of PDAs (Personal Digital Assistants) using Android’s own sensor technologies. An attempt is made to determine the approximate position of the device indoors using accelerometers, gyroscopes and magnetometers which are the inertial sensors provided by the Android system.